T-cell receptor variable region gene usage in T-cell populations. - Garman, R D (1986)
We have examined T-cell receptor alpha- and beta-chain variable (V) region gene usage in T-cell populations predicted to have different major histocompatibility complex-restriction specificities. Using a sensitive ribonuclease protection assay to measure T-cell receptor mRNA levels, we found no striking differences in the usage of three V alpha genes and three V beta genes in T-cell populations from three congeneic H-2-disparate strains of mice and between the mutually exclusive Ly2+ L3T4- and Ly2- L3T4+ T-cell subpopulations. These results suggest that major histocompatibility complex restriction cannot be explained by the differential usage of nonoverlapping V alpha or V beta gene pools. In contrast, striking but unpredictable differences were seen in V gene usage in populations of T cells selected by activation with particular alloantigens.